What Does Service Mean? Or, What Can We Ask of Market and Governmental Actors?. Issue 1 (2nd January 2017) - Zhang, Qianyou
ABSTRACT: Public administration is about serving the public, but public administration scholars have been virtually silent about the definition of public service. This article describes a normative conception of service that can help in judging whether government and market actors serve their constituents and clients. Traditionally, public administration scholars have focused primarily on the public aspect of public service and have attempted to make all organizations public. This article, however, focuses on the service dimension of public service and argues that if all organizations serve their clients, it is not necessary for all organizations to be public.